Kohesi Gramatikal Dalam Kumpulan Kisah Nyata 25 Nabi DAN Rosul Karya Cecep Ihsani - Mursida, Mursida (EL-EMIR Institute, 2025)
This study aims to identify the forms of grammatical cohesion found in The True Stories of 25 Prophets and Messengers, particularly focusing on the types of grammatical cohesion so that readers can recognize the parts involving reference, substitution, ellipsis, and conjunction. This research is a descriptive qualitative study. The object of the research is the discourse in The True Stories of 25 Prophets and Messengers. Based on the research findings, it is concluded that the grammatical cohesion found in The True Stories of 25 Prophets and Messengers, especially in the stories of Prophet Lot (Luth) AS, Prophet Jacob (Yaqub) AS, and Prophet Ezekiel (Zulkifli) AS, includes: (1) 25 instances of reference, which consist of both anaphoric and cataphoric references; (2) 95 instances of substitution; (3) 5 instances of ellipsis; and (4) 115 instances of conjunction. These findings indicate that the use of grammatical cohesion plays a significant role in shaping the coherence of the discourse.